Integración de las TICs en el perfil profesional: la experiencia de la Carrera de Sistemas de Información en Salud (Repertorio Científico, 2024)
The objective of this article is to present the relationship between the trends in ICTs applied to the field of health sciences and the new Health Information Systems career, based on the updating of the professional profile and the design of the new curriculum that integrates key skills and abilities for the training of professionals. The methodology is based on an exploratory study carried out on a probabilistic sample of active students and graduates of the Health Records and Statistics course (REDES) to whom a digital questionnaire was applied between 2021 and 2022. The responses to the questionnaires made it possible to construct a demographic profile of the students, job characteristics and assessment of the skills and abilities acquired for the administration of Health Information Systems, among others. It is concluded that REDES is characterized by having a young and highly feminized student body, located mainly in areas far from the Greater Metropolitan Area (GAM) and that most of them are still trying to find a job niche, although the horizon of employability continues to be dominated by public institutions and the existing opportunities in the private sector are unknown, it is expected that with the transition to the new career, the gap identified in the area of ICTs will decrease.
Keywords: National Health System, Health, ICTs, REDES, HIS, Professional profile